Working with unmarried pregnant young women and teenagers in Malaysia: Implications for researchers - Hillaluddin, Azlin Hilma; Mat Saad, Zarina (2014)
Premarital pregnancy continues to be a social dilemma within the Malaysian society.The increasing statistics of babies being born without a legally registered father’s name presents the legal, health and welfare problems associated with the effects of premarital pregnancy.The need to study this social problem requires not only a receptive understanding of the problem, but also the researcher’s preparation in terms of skills and mental preparedness.The authors conducted a research aimed at understanding premarital pregnancy experiences of those who decided to seek protection in women shelters.A total of 101 young women and teenagers from five women shelters in Malaysia participated in the research. Ethical consideration is highly essential when conducting research with this group of individuals since the focus of such research may at times touch upon sensitive issues or potentially brings up traumatic experience.The focus of this paper is a discussion of the authors’ experience regarding the ethical dilemma and preparation when conducting the research.This paper intends to highlight important issues that may be of guideline to other researchers who wish to conduct similar research with this group of participants.